Cardiac sympathetic overdrive, M2 macrophage activation and fibroblast heterogeneity are associated with cardiac remodeling in a chronic pressure overload rat model of HFpEF - Sun, Fengjiao; Yuan, Ling; Wang, Zi; Cui, Xiaoxue; Lv, Nan; Zhang, Ting; Zhang, Yan; Cai, Jun (Frontiers in Pharmacology, 2024)
Heart failure with preserved ejection fraction (HFpEF) is a multifaceted pathogenesis disease and the exact mechanisms driving HFpEF have not been completely elucidated. Pressure overload hypertrophy (POH) related fibroblasts and M2 macrophages in HFpEF myocardium have been recently identified and are now of great interest. Sympathetic overdrive has also been implicated in HFpEF. This study is designed to dynamically observe the potential roles of aforementioned mechanisms in pathological remodeling and cardiac dysfunction in chronic PO rats. Surgical constriction of the abdominal aorta was used for induction of HFpEF. Echocardiography, electrocardiogram, hemodynamic measurement, hematoxylin and eosin staining, Masson staining, immunohistochemistry and immunofluorescence were performed to assess the changes in heart dysfunction, cardiac remodeling and driving mechanisms at different time points (2, 18, 24 weeks). The PO induced HFpEF model was well established, which was confirmed by the persistent increase in carotid artery systolic and diastolic blood pressure, and left ventricle hypertrophy at the corresponding postoperative stage. Meanwhile, PO hypertrophy gradually developed into HFpEF, associated with QT and QTc intervals prolongation, normal systolic (EF was maintained at >50%) but impaired diastolic function (increasing LVEDP and LV -dP/dtmin, abnormal E/A ratio), increased myocytes size, and observed relatively slight inflammatory infiltration but robust reactive fibrosis. IHC staining further confirmed that macrophages (CD68) but not neutrophils (MPO) or T cells (CD3) accounted for a predominant proportion of infiltrating cells. Mechanistically, we found that the infiltrating macrophages in the heart expressed high levels of CD206 which was simultaneously adjacent to POH fibroblasts appeared to overexpression of α-SMA in PO rats at late stages. Interestingly, we distinguished two different POHF sub-populations during PO induced HFpEF development, according to non overlapping signals of α-SMA and PDGFRα/β proteins. Additionally, PO led to a pronounced exaggeration in sympathetic fibers at all time points. These findings suggest that the establishing model here begins with cardiac sympathetic overdrive, subsequently along with immune cells especially M2 macrophage accumulation and fibroblast heterogeneity at later stages is associated with the development of cardiac maladaptive remodeling and diastolic dysfunction thus further progression to HFpEF.